Młodzież akademicka jako reprezentant nowej fazy w rozwoju. O kondycji tożsamości w okresie młodzieńczości - Ławiak, Alicja (Kultura-Społeczeństwo-Edukacja, 2020)
Ławiak Alicja, Academic youth as a representative of a new phase in a social development. About the condition of identity in youthfulness. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 235–244, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.15. The post-modern reality, including the multitude of changes and expanding volumes of offers force the individual to continually redefine themselves. A person existing in contemporary reality is permanently on the search for their identity, in order to finally find the most suitable one, which (as it usually turns out nowadays) does not exist. Youths make a choice within the range of education offers. They more often than not decide to study, with studying being the reason for delaying the moment of entry into adulthood and taking over social roles that are specific for the period of young adulthood. In making this choice, young people enter the phase of so-called emerging adulthood, which for a while now has been a new, separate phase of development, fitting in between adolescence and young adulthood. They are not passing through the complex process of puberty any more, however, they do not always have a mature identity. They find themselves in a period characterised by intense exploration. The article attempts to describe the specifics of this stage, additionally presenting an overview of studies on the mode of coping with issues of identification characterising the early adulthood period.